Phenomena and Implications of Panai Money in Marriage in Datara Village, Bontoramba District, Jeneponto Regency (Cultural Da’wah Perspective) - Juhansyah, Juhansyah; Jasad, Usman; Muhammad, Firdaus (Jurnal Mercusuar, 2021)
The main problem in this thesis is the phenomenon and implications of uang panai (bride wealth) on marriage in Datara Village, Bontoramba Sub-district, Jeneponto Regency, while the research focus is on cultural da’wah, including its forms, materials, and strategies. This main problem is then divided into several sub-problems, namely: 1. How do people understand uang panai? 2. What are the implications of uang panai on marriage? 3. How is cultural da’wah implemented to provide understanding to the community regarding the tradition of uang panai in accordance with Islamic values